Cardiovascular risk management in patients with active Ankylosing Spondylitis: a detailed evaluation - Heslinga, Sjoerd C (BMC Musculoskelet Disord, 2015)
BACKGROUND: Ankylosing spondylitis (AS) is an inflammatory disease with documented elevated cardiovascular (CV) risk due to systemic inflammation and a higher prevalence of CV risk factors. CV risk management (CV-RM) could be an effective method to reduce CV mortality and morbidity in AS patients. We assessed CV risk and evaluated guideline adherence according to the Dutch CV-RM guideline. METHODS: This study was conducted with a cohort of consecutive AS patients eligible for treatment with a tumor necrosis factor (TNF) -α inhibitor. Data from the Dutch National Institute for Public Health and Environment was used to compare the prevalence of CV risk factors in AS patients with the Dutch background population. RESULTS: In total, 254 consecutive AS patients were included. The prevalences of hypertension (41% vs 31%) and smoking (43% vs 27%) were substantially higher in AS patients as compared to the general Dutch background population. Of 138 AS patients older than 40 years the 10-years CV risk could be calculated. Fifty-one of these 138 patients (37%) had an indication for CV risk treatment. CV risk treatment was initiated in 42 of the 51 (82%), however, in only 12 of the 51 (24%) patients treatment targets for either hypertension or hypercholesterolemia were reached. CONCLUSION: The increased rates of hypertension and smoking illustrate the importance of CV-RM in AS patients. Although the majority of all AS patients eligible for CV-RM received CV risk medication, CV-RM remains a challenge for treating physicians, as treatment targets were not achieved in three-quarter of the eligible patients.